Spreading of struma ovarii tumour via a lumbo-peritoneal shunt: first case report and short review of the literature. (1st November 2020) - Frantzias, Joseph; Polyzoidis, Stavros; Rajagopal, Shobha; Bullock, Peter
Abstract: Neurosurgical shunts occasionally act as a conduit for seeding of central nervous system tumours to the abdomen. Retrograde spread of extra-neural tumours to the central nervous system is exceedingly rare. We report the first case of an abdominal primary tumour spreading to the spinal cord via a lumbo-peritoneal shunt. This is also the first case report of a struma ovarii tumour metastasis to the central nervous system via any route.